Anthropologist as Nomad: Introducing a New Co-Editor. Issue 1 (1st March 2022) - Bošković, Aleksandar
Abstract : My anthropological journey has consisted in movement not only between different disciplines, but also between languages, countries and continents. This has involved stories of identity (imagined, constructed, or both), changes of place (teaching in six countries on three continents, and in four languages), searches for a safe haven, and belief in understanding the motives that govern human beings. In this wonderful journey, my coming to the Anthropological Journal of European Cultures seems almost an inevitable event. Or perhaps it is just a product of 'chance and serendipity'. In retrospect, I look at my anthropological journey so far as a voyage of discovery – to different places, under different circumstances and in very different parts of the world.